A mega review of cultural studies : linking leadership to corporate governance - Evans, Gary Llewellyn (Economics and Business Review, 2014)
This paper take us through the history of culture research with five top researchers in the field and how their culture theories are structured and the debate that has occurred on the application of cultural dimensions. This paper takes the unique perspective of corporate boards and considerations required in the application of cultural dimensions within the boardroom. Research of board culture is only starting to occur and to be effective we need to consider the history of cultural research and how we can apply this knowledge to the board environment going forward. As we enter 2014 the search is on by both academics and practitioners on how to better understand the role of culture within our corporate boards. (original abstract)